Resale in Second-Price Auctions with Costly Participation - Gorkem Celik; Okan Yilankaya (Koç University-TÜSİAD Economic Research Forum (ERF), 2015)
We investigate efficiency properties of sealed-bid second-price auctions with costly participation and resale. Each bidder chooses to participate in the auction if her valuation is higher than her optimally chosen participation cutoff. If resale is not allowed and the bidder valuations are drawn from a strictly convex distribution function, the symmetric equilibrium (where all bidders use the same cutoff) is less efficient than a class of two-cutoff asymmetric equilibria. Existence of these equilibria without resale is sufficient for existence of similarly constructed two-cutoff equilibria with resale. Moreover, these equilibria with resale are ?more asymmetric? and (under a sufficient condition) more efficient than the corresponding equilibria without resale.
Keywords: C72; D44; D82; 330; Second-price auctions; resale; participation cost; endogenous entry; endogenous valuations